2023
DOI: 10.18421/tem123-51
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning With Discord Application as Creative Teaching

Mohammad Salehudin,
Zurqoni Zurqoni,
Robingatin Robingatin
et al.

Abstract: Teacher creativity in teaching using technology such as mobile learning has been widely applied in developed countries, because it is a 21st century skill. However, only a few lecturers in developing countries, such as Indonesia, are incorporating mobile learning with technological tools, like the Discord application, to create a stimulating and interactive learning experience for their students. For data collection, a questionnaire comprising 26 questions with 6 scales was used. The questionnaire was sourced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 52 publications
1
5
0
1
Order By: Relevance
“…The three most frequent classes of age were between 25 and 29 years old (16), between 30 and 34 (14), and between 35 and 39 (8). The remaining classes of ages had 3 students (40-44 and 45-49), 2 (20)(21)(22)(23)(24), and 1 (50-54, 55-59). Five students did not disclose their age.…”
Section: Study Participants and Contextual Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The three most frequent classes of age were between 25 and 29 years old (16), between 30 and 34 (14), and between 35 and 39 (8). The remaining classes of ages had 3 students (40-44 and 45-49), 2 (20)(21)(22)(23)(24), and 1 (50-54, 55-59). Five students did not disclose their age.…”
Section: Study Participants and Contextual Resultsmentioning
confidence: 99%
“…Hence, the EduCITY app prototype created a positive impression regarding Attractiveness (1.43), Perspicuity (1.11), Stimulation (1.18), and Novelty (1.02), and a neutral-positive impression on the Efficiency (0.87) and Dependability (0.73) scales. Other studies on user experience of mobile apps have found positive user experience values [18][19][20][21].…”
Section: User Experience With a Mobile Augmented Reality Appmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, Discord was modified for educational purposes, evidencing its effectiveness as a free platform for this purpose (Uong et al, 2022). In developing countries, few educators adopt mobile teaching through technological tools like Discord to offer students a dynamic and interactive learning experience (Salehudin et al, 2023b). One of the beneficial features of the Discord app lies in its accessibility and convenience, especially on mobile devices, thanks to its compact size (Salehudin et al, 2023b).…”
Section: Discordmentioning
confidence: 99%
“…In developing countries, few educators adopt mobile teaching through technological tools like Discord to offer students a dynamic and interactive learning experience (Salehudin et al, 2023b). One of the beneficial features of the Discord app lies in its accessibility and convenience, especially on mobile devices, thanks to its compact size (Salehudin et al, 2023b). In addition, Discord makes communication easy, easy to use and with its ability to create work groups, text and voice options (Pardines-Lence et al, 2023).…”
Section: Discordmentioning
confidence: 99%